Comparison between the modified long gonadotropin-releasing hormone agonist protocol and the non-downregulation protocol in POSEIDON groups: a propensity score matching retrospective cohort study - Chen, Chunyan; Zeng, Xinliu; Zhang, Hanke; Wei, Qiongqiong; Gao, Ying; Liu, Lin (Frontiers in Endocrinology, 2023)
Background: In vitro fertilization (IVF) is the main technique to address the infertility issue in the Poseidon population. Adopting appropriate protocols for assisted reproduction technologies (ART) cycles in the Poseidon group may attain more favorable pregnant outcomes. Objectives: This study aimed to compare the effectiveness of modified long gonadotropin-releasing hormone agonist protocol and non-down-regulation protocol in Poseidon patients undergoing ART, and to identify the factors affecting the pregnancy outcomes in this group. Design: Propensity score-matched (PSM) retrospective analysis. Participants: This study cohort consisted of 910 patients diagnosed with ovarian hyporesponsiveness and treated by IVF from January 2020 to June 2022. They were followed up until the transfer of the last embryo of the IVF cycle and/or pregnancy at 12 weeks. The study was conducted at the